Food environment of bus terminals in the Rio de Janeiro metropolitan region - Ana Carolina Castro de Jesus; Laís Vargas Botelho; Daniela Silva Canella; Letícia Ferreira Tavares; Paulo César Pereira de Castro Junior; Isabela da Costa Gaspar da Silva; Letícia de Oliveira Cardoso (Universidade de São Paulo, 2024)
ABSTRACT PURPOSE To describe and analyze the healthiness of formal and informal food establishments in bus terminals of the metropolitan region of the state of Rio de Janeiro. METHOD An audit was conducted in 156 formal and 127 informal food establishments located in 14 bus terminals of the five most populous cities of the metropolitan region of Rio de Janeiro. Proportions of types of establishments and means (95%CI) of food availability indicators in formal and informal settings were calculated. For the formal setting, prices, proportions of accepted payment methods, days and hours of operation, and food categories with displayed advertising were described. RESULTS The healthiness of food establishments in bus terminals was low (less than 36%). On average, ultra-processed food subgroups were 250% more available for purchase than fresh or minimally processed food. Purchasing food at these places was convenient because several forms of payment were available, and the opening hours of the establishments followed the peaks of movement. In addition, 73.3% of the advertising referred to ultra-processed drinks, and the cost-benefit of buying ultra-processed food was better than fresh or minimally processed food. CONCLUSION The food environment of bus terminals in the metropolitan region of Rio de Janeiro promotes unhealthy eating. Regulatory public policies should focus on initiatives to limit the wide availability and advertising of ultra-processed food in spaces of great circulation of people.